2019
DOI: 10.1021/acs.cgd.9b00951
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser-Induced Nucleation of Sodium Chlorate at High Energy Densities

Abstract: We report on a study of laser-induced nucleation (LIN) of sodium chlorate in supersaturated aqueous solutions using focused nanosecond laser pulses at high energy densities (420 kJ cm -2 ). On irradiation with a single laser pulse, optical breakdown was observed in the form of a luminous plasma, and numerous microbubbles were produced. Based on the observations, we estimate the energy threshold for optical breakdown in the solutions to be 70 J cm -2 . Remarkably, even at high energy densities, single laser pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Since then, a considerable number of studies have been reported with various types of chemical compounds and by employing an array of laser systems whose properties/parameters including time duration (continuous, femtosecond, picosecond, nanosecond regime), field polarization (linear, circular and elliptical), wavelength (UV–vis–IR), or intensity (ionizing, nonionizing), were altered to control primary nucleation. However, despite the remarkable scientific progress, the underlying mechanism behind the laser-induced nucleation still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a considerable number of studies have been reported with various types of chemical compounds and by employing an array of laser systems whose properties/parameters including time duration (continuous, femtosecond, picosecond, nanosecond regime), field polarization (linear, circular and elliptical), wavelength (UV–vis–IR), or intensity (ionizing, nonionizing), were altered to control primary nucleation. However, despite the remarkable scientific progress, the underlying mechanism behind the laser-induced nucleation still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They succeeded in inducing forced crystallization from a supersaturated solution of urea by shooting a nanosecond near-infrared laser pulse into the solution. Since this first demonstration, the method has been extended to various systems, providing a variety of classifications and mechanisms such as the optical Kerr effect mechanism, , which contributes to the forced alignment of molecules in subcritical clusters by the electrical-field oscillation of an incident pulsed laser, and the cavitation bubble mechanism, in which a femtosecond laser-induced cavitation bubble increases the local concentration of the solution at the bubble/solution interface. Although these mechanisms of crystallization controlled with pulsed lasers are not yet fully understood, the pulsed lasers have succeeded in the spatiotemporal control of nucleation, polymorph control by manipulating laser polarization, the crystallization of a macromolecule with an unknown structure, and the control of the crystal growth mode and the crystal shape of a growing crystal by introducing a dislocation in the crystal. , The research field of light-induced crystallization, which began with the irradiation of a nanosecond pulsed laser, is still being developed by changing the experimental conditions and the target phenomena, such as the pulse duration, wavelength of incident laser, compounds, nucleation, and crystal growth, leading to the creation of a practical method to induce crystallization from a supersaturated solution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the impurity of the solution has impact on the laser-induced nucleation results . These methods differ from the electromagnetic field-induced nucleation as they are independent of laser polarization. , Except for NPLIN, a focused high-power nanosecond laser can induce optical breakdown in solution and induce the nucleation of sodium chlorate . A femtosecond laser has been a useful tool in physical and chemical fields owing to its ultrashort pulse width and extremely high peak intensity .…”
Section: Introductionmentioning
confidence: 99%
“…11,23 Except for NPLIN, a focused high-power nanosecond laser can induce optical breakdown in solution and induce the nucleation of sodium chlorate. 24 A femtosecond laser has been a useful tool in physical and chemical fields owing to its ultrashort pulse width and extremely high peak intensity. 25 nanosecond laser, femtosecond laser pulses can be absorbed by transparent materials.…”
Section: Introductionmentioning
confidence: 99%